A Systematic Literature Review on Developing a Parenting Toolkit to Enhance Motivation among Parents of Children with Autism Spectrum Disorder - Murniwati Laia; Marlina Marlina; Rahmahtrisilvia Rahmahtrisilvia; Mega Iswari Binah Asnah; Murniwati Laia; Marlina; Rahmahtrisilvia Rahmahtrisilvia (Universitas Negeri Malang, 2026)
This study aims to review scientific literature on parenting toolkit development as a strategy to enhance motivation among parents of children with Autism Spectrum Disorder (ASD). This study employs a Systematic Literature Review (SLR) approach following the PRISMA protocol, complemented by bibliometric analysis using Biblioshiny. Data were retrieved from Scopus and Google Scholar databases within the publication range of 2016–2025. Out of 835 identified articles, 31 met the inclusion criteria and were analyzed further. Analysis shows accelerated global publication trends in ASD parenting interventions during 2024–2025. Four thematic clusters revealed that parenting stress directly diminishes parental self-efficacy and motivation. Most existing interventions are rigid, time-intensive, and clinically face-to-face, leaving caregivers highly vulnerable to burnout. Although limited to Scopus and Google Scholar, this study theoretically underscores the critical need to shift from child-centered behavioral mechanics toward parent-mediated interventions that reinforce the caregiver's internal psychological constructs. Practically, it provides empirical guidance for practitioners to design flexible, self-mediated family support tools by simplifying instructions and incorporating accessible delivery methods like telehealth. Socially, sustaining parental motivation enhances the quality of life and emotional resilience of families raising children with ASD, reducing the risks of diagnosis denial and therapy discontinuation. The originality lies in combining thematic bibliometric mapping with qualitative synthesis to provide a scientific justification for developing a